IMPLEMETASI MANAJEMEN RANTAI NILAI HALAL DIMASA KENORMALAN BARU: STUDI PADA BADAN USAHA MILIK PESANTREN AL MUMTAZ KABUPATEN GUNUNGKIDUL - Indra Gunawan; Maryono Maryono (JURNAL MANAJEMEN DAKWAH, 2022)
The purpose is to analyze the benefits and management of the halal value chain at BUMP Al Mumtaz, Gunungkidul Regency, and to describe the use of halal value chain management at Islamic boarding schools in the new normal. This research is qualitative descriptive field research. Data sources for the study include interviews, books, journals, magazines, photo documentation, and other similar records. Test the validity of the research data, namely dependability, transferability, dependability, and confirmability. The data analysis technique used interactive analysis with data collection from observation, interviews, and documentation. The results study of the first is a synergy between supporting activities that optimally support the main activities in the supply chain. The guarantee of the halal ecosystem has been optimized with the existence of halal activities in value chain management implemented from the production, distribution, and consumption processes. Thus, it can create production effectiveness in Al Mumtaz BUMP business units from upstream to downstream, especially during the new normal. Second, the advantages can identify from the optimal management of pesantren resources in supporting halal value chain activities and the constraints faced due to the limited resources owned by PPT Al Mumtaz.